2013
DOI: 10.5152/akd.2013.235
|View full text |Cite
|
Sign up to set email alerts
|

Association of mitral annular calcification with endothelial dysfunction, carotid intima-media thickness and serum fetuin-A: an observational study

Abstract: Objective: Mitral annular calcification (MAC) is characterized by degenerative calcification of the mitral valve annulus. Atherosclerosis plays role in progression of MAC. Fetuin A is the inhibitor of pathological calcification. In the present study, we investigated the relationship between MAC and fetuin A with carotid intima media thickness (CIMT) and endothelial dysfunction. Methods: In this observational cross-sectional study, 40 patients with documented MAC on transthoracic echocardiography (TTE) and 40 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…As a known fact, in the pathophysiology of atherosclerotic cardiovascular diseases, increased inflammation, and endothelial dysfunction play fundamental roles [26]. Outcomes of this study suggest that NLR may be one of the markers of endothelial dysfunction, and inflammation in obese patients.…”
Section: Discussionmentioning
confidence: 80%
“…As a known fact, in the pathophysiology of atherosclerotic cardiovascular diseases, increased inflammation, and endothelial dysfunction play fundamental roles [26]. Outcomes of this study suggest that NLR may be one of the markers of endothelial dysfunction, and inflammation in obese patients.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, decreased serum fetuin-A and albumin levels are associated with the development of coronary artery disease and heart valve calcification505152535455565758. Therefore, the risk factors of atherosclerosis and heart valve calcification are identical to those promoting the formation of CPB in the human blood.…”
Section: Discussionmentioning
confidence: 99%
“…NLR, considered to be an indicator of subclinical inflammation, is an indicator which is calculated by using neutrophil and lymphocyte values in the hemogram and of which popularity is increasing with each passing day (25). Increased inflammation and endothelial dysfunction play an important role in the pathophysiology of atherosclerotic cardiovascular diseases (26). Aydın et al (27) found out that NLR was higher in obese adolescents than the healthy control group.…”
Section: Discussionmentioning
confidence: 99%